Site characterization for the design of thermoactive geostructures - Vieira, Ana; Alberdi-Pagola, Maria; Barla, Marco; Christodoulides, Paul; Florides, Georgios A.; Insana, Alessandra; Javed, Saqib; Maranha, João Ribas; Milenic, Dejan; Prodan, Iulia; Salciarini, Diana (My University, 2022)
This paper addresses the topic of site characterization for the design of Shallow Geothermal Energy (SGE) systems, namely of thermoactive geostructures, which are geotechnical structures, such as piles, retaining walls and tunnel linings, also used as heat exchangers as part of closed-loop SGE systems. Such solutions, being increasingly adopted for buildings’ and infrastructures’ heating and/or cooling, are considered sustainable and cost effective. For the design of the primary circuit of the SGE system, which is embedded within the superficial soil layers, a comprehensive knowledge of the ground condition at the site is mandatory. This includes the evaluation of the energy features and whether the system can provide the required energy needs during the operational period, as well as the verification of the structural and geotechnical safety and functionality requirements. The site characterization for SGE systems involves different stages, from desk studies to detailed characterization, including in-situ trials, laboratory testing of undisturbed soil samples and the study of possible interferences. The specific aspects that will be addressed are: (i) the assessment of the site undisturbed ground temperature and its hydrogeological features; (ii) the thermal and thermomechanical characterization of the different soil layers; (iii) the investigation of the ground-heat exchanger thermal resistance; (iv) the collection of information related to the environmental constraints and to potential interferences among multiple users, which are related to the service life of the structure. The overall aim is to ensure a proper design of the SGE system for guaranteeing its sustainability in the long term.
Keywords: Shallow geothermal energy; Thermoactive geostructures; Site thermal characterization; Undisturbed ground temperature; Thermal conductivity